Eye-tracking the effect of word order in sentence comprehension in aphasia: evidence from Basque, a free word order ergative language. Issue 10 (26th November 2017) - Arantzeta, Miren; Bastiaanse, Roelien; Burchert, Frank; Wieling, Martijn; Martinez-Zabaleta, Maite; Laka, Itziar
ABSTRACT: Agrammatic speakers of languages with overt grammatical case show impaired use of the morphological cues to establish theta-role relations in sentences presented in non-canonical word orders. We analysed the effect of word order on the sentence comprehension of aphasic speakers of Basque, an ergative, free word order and head-final (SOV) language. Ergative languages such as Basque establish a one-to-one mapping of the thematic role and the case marker. We collected behavioural and gaze-fixation data while agrammatic speakers performed a picture-matching task with auditorily presented sentences with different word orders. We found that people with aphasia (PWA) had difficulties in assigning theta-roles in Theme-Agent order. This result is in line with processing accounts. Contrary to previous findings, our data do not suggest a systematic delay in the integration of morphological information in the PWA group, but strong reliance on the ergative case morphology and difficulties assigning thematic roles into the determiner phrases.